2014
DOI: 10.1515/hmbci-2014-0025
|View full text |Cite
|
Sign up to set email alerts
|

5α-Reductase inhibitors alter steroid metabolism and may contribute to insulin resistance, diabetes, metabolic syndrome and vascular disease: a medical hypothesis

Abstract: 5α-reductases, a unique family of enzymes with a wide host of substrates and tissue distributions, play a key role in the metabolism of androgens, progestins, mineralocorticoids and glucocorticoids. These enzymes are the rate-limiting step in the synthesis of a host of neurosteroids, which are critical for central nervous system function. Androgens and glucocorticoids modulate mitochondrial function, carbohydrate, protein and lipid metabolism and energy balance. Thus, the inhibition of these regulatory enzymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 56 publications
0
21
0
1
Order By: Relevance
“…This finding suggests that inhibition of 5α-Rs in liver brings about biochemical changes in liver function and may represent alterations in liver metabolism [90][91][92]. In addition, finasteride inhibits not only type 2 but also type 1 5α-reductase, albeit at a slower rate, suggesting that this drug may alter liver function via inhibition of 5α-reductases types 1 and 2 [93][94].…”
Section: Resultsmentioning
confidence: 99%
“…This finding suggests that inhibition of 5α-Rs in liver brings about biochemical changes in liver function and may represent alterations in liver metabolism [90][91][92]. In addition, finasteride inhibits not only type 2 but also type 1 5α-reductase, albeit at a slower rate, suggesting that this drug may alter liver function via inhibition of 5α-reductases types 1 and 2 [93][94].…”
Section: Resultsmentioning
confidence: 99%
“…Since no treatment of hypogonadism were implemented in the BPH patients in such studies, it remains difficult to ascertain the nature of the adverse sexual side effects. Although review of the literature reported serious concerns about the potential side effect of 5α-RIs therapy [23], such concerns were not heeded. In fact, many continue to argue that since clinical trial reports did not show significant adverse effects, the drug is deemed safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…GCs are metabolized by reduction of the A ring via 5α-Rs and then cleared via specific pathways involving conjugation and excretion. The principal urinary metabolites of cortisol and cortisone are tetrahydrocortisol and tetrahydrocortisone, cortols and cortolones [23].…”
Section: Peripheral Physiological Effects Of 5α-rs Activitiesmentioning
confidence: 99%
See 2 more Smart Citations